Slovenci v Mendozi - Mlekuž, Jernej (Geografski vestnik, 2000)
The scope of the present paper is to adress the role of the "source" place in the process of shaping ethnical and national identity among Slovenian emigrant community in Mendoza, Argentina.
Keywords: demogeografija; human migration; migracije; slovenski izseljenci; narodna identiteta; Slovenci; Slovenes; Argentina; Mendoza